Temporal Fluctuation of Mood in Gaming Task Modulates Feedback Negativity: EEG Study With Virtual Reality - Yokota, Yusuke; Naruse, Yasushi (Frontiers in Human Neuroscience, 2021)
Feedback outcomes are generally classified into positive and negative feedback. People often predict a feedback outcome with information that is based on both objective facts and uncertain subjective information such as a mood. For example, if an action leads to good results consecutively, people performing the action overestimate the behavioral result of the next action. In electroencephalogram measurements, negative feedback evokes negative potential, called feedback negativity, and positive feedback evokes positive potential, called reward positivity. The present study investigated the relationship between the degree of the mood caused by the feedback outcome and error-related brain potentials. We measured the electroencephalogram activity while the participants played a virtual reality shooting game. The experimental task was to shoot down a cannonball flying towards the player using a handgun. The task difficulty was determined from the size and curve of the flying cannonball. These gaming parameters affected the outcome probability of shooting the target in the game. We also implemented configurations in the game such as the player’s life-points and play times. These configurations affected the outcome magnitude of shooting the target in the game. Moreover, we used the temporal accuracy of shooting in the game as the parameter of the mood. We investigated the relationship between these experimental features and the event-related potentials using the single-trial based linear mixed effect model analysis. The feedback negativity was observed at an error trial, and its amplitude was modulated with outcome probability and the mood. Conversely, reward positivity was observed at hit trials, but its amplitude was modulated with outcome probability and outcome magnitude. This result suggests that the feedback negativity is enhanced not only according to feedback probability but also according to the mood that was changed depending on the temporal gaming outcome.